Hand-arm strength and endurance as predictors of climbing performance - Baláš, J.; Pecha, O.; Martin, A. J.; Cochrane, D. (European Journal of Sport Science, 2012)
The aims of this study were to examine training characteristics, body composition, muscular strength, and endurance in sport climbers, and to demonstrate the relationship among these components by means of structural equation modelling. Altogether, 205 sport climbers (136 males, 69 females), with a performance RP (red point) of grade 4 to 11 on the Union Internationale des Association d'Alpinisme (UIAA) scale, took part in the study. The proposed structural model, with latent variable hand-arm strength and endurance (developed from reference values for simple tests), indicated by three manifest variables (grip strength, bent-arm hang, and finger hang) and three exogenous variables (body fat, volume of climbing, and climbing experience), explained 97% of the variance in climbing performance. The relationship between body fat and climbing experience/volume with climbing performance was not direct, but was better explained using the mediator hand-arm strength and endurance. We conclude that these simple tests, together with percent body fat, volume of climbing, and climbing experience, can satisfactorily predict climbing performance.